(untitled) (Encuentros, 2023)
The Saber Test is a mechanism used by the Colombian Ministry of Education to measure student learning on an annual basis. Its results provide information that can be used by educational institutions to modify the institutional curriculum. In that sense, the objective of this study is to analyze the results of the department of Chocó in the area of mathematics in the period between 2016 and 2021 to show the need to review the educational policy. We make use of a qualitative analysis of the 164 schools in the department. The results show a slight improvement in the handling of quantitative and schematic information, but with historical difficulties in the validation of procedures that go beyond the algorithmic.